2000
DOI: 10.1590/s0041-87812000000200003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body fluid and energy compartments during prolonged hunger strike

Abstract: 1) All compartments diminished during fasting, but body fat was by far the most affected; 2) Total water was low and total body resistance comparatively elevated, but these findings rapidly reversed upon rehydration; 3) Exaggerated fat percentage estimates from BIA tests and simultaneous increase in lean body mass estimates suggested that this method was inappropriate for assessing energy compartments in the studied population; 4) Patients were not morphologically malnourished after 43 days of fasting; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Deaths from starvation are commonly reported after more than 6 weeks of total lack of food. 4,5 In practice, it seems that deaths and serious injuries among subjects exposed to a survival situation often are the result of exposure or risky behavior. 6,7 Therefore, factors contributing to poor judgment should be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…Deaths from starvation are commonly reported after more than 6 weeks of total lack of food. 4,5 In practice, it seems that deaths and serious injuries among subjects exposed to a survival situation often are the result of exposure or risky behavior. 6,7 Therefore, factors contributing to poor judgment should be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In relation to the deaths of 10 Irish Republican Army hunger strikers in 1981, fasting survival was dependent on fat more than protein stores. 20 In a another group of eight hunger strikers, Faintuch observed the overwhelming participation of body lipids in maintaining energy balance during uncomplicated prolonged starvation, 21 once again highlighting the crucial importance of fat stores during inadequate nutrition.…”
mentioning
confidence: 99%
“…The longitudinal studies included suggested that BF reductions seen between general preparation and competition phases ranged between 30 and 60% (Table 1), with decreases of up to 70% reported for single individuals (6). Similar reductions of 20-35% for bariatric surgery (2,5) and 60% following prolonged hunger strike (7) have been only reported occasionally and are considered to be extreme circumstances.…”
Section: Discussionmentioning
confidence: 94%